Konsumsi Simbolis dalam Pemilikan Rumah oleh Kelas Menengah (Studi Kasus Penghuni Greenland Forest Park Residence Depok) - Rahman, Tyka (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2017)
This study explains about symbolic consumption of middle class for home ownership. This study used the qualitative approach, it was chosen as the purpose of this study is to explain how the middle class colours their class position through the home ownership. Data was collected through observation and depth interview for the strategy of inquiry. The subject of study was dweller of Greenland Forest Park Residence. The research was conducted from April to July 2015.Gerke (2002) explained about lifestyling of Indonesian middle class as a strategy to show their social class without real consumption. This study revealed that the home ownership show two aspects of middle class (Greenland dweller) consumption; the real and symbolic consumption at the same time demonstrating their social class.